Colloidal assembly in droplets: structures and optical properties. Issue 36 (10th September 2020) - Park, Sanghyuk; Hwang, Hyerim; Kim, Minjung; Moon, Jun Hyuk; Kim, Shin-Hyun
Abstract : This review highlights recent progress in emulsion-templated colloidal clustering, especially focusing on novel structures of icosahedral, decahedral, and single-crystalline clusters. Abstract : Colloidal assembly in emulsion drops provides fundamental tools for studying optimum particle arrangement under spherical confinement and practical means for producing photonic microparticles. Recent progress has revealed that energetically favored cluster configurations are different from conventional supraballs, which could enhance optical performance. This paper reviews state-of-the-art emulsion-templated colloidal clusters, and particularly focuses on recently reported novel structures such as icosahedral, decahedral, and single-crystalline face-centered cubic (fcc) clusters. We classify the clusters according to the number of component particles as small ( N < O (10 2 )), medium ( O (10 2 ) ≤ N ≤ O (10 4 )), and large ( N ≥ O (10 5 )). For each size of clusters, we discuss the detailed structures, mechanisms of cluster formation, and optical properties and potential applications. Finally, we outline current challenges and questions that require further investigation.